Speed estimation in forward scattering radar by using Standard Deviation method - Salah, Mutaz; A. Rasid, Mohd Fadlee; Raja Abdullah, Raja Syamsul Azmir; Cherniakov, M. (Canadian Center of Science and Education, 2009)
Forward Scattering Radar (FSR) is a special type of Radar. The interest in FSR is rises after its capability in target classification is validated. Unfortunately, the speed of the target still not been solved. Thus, this paper proposed a method to estimate speed FSR system. The theory of FSR systems is briefly described together with practical experiments to evaluate the feasibility of such a system in real-life scenarios. All data are collected from the practical experimentation by using typical ground vehicle as target (e.g. car, lorry). In the proposed system, Standard Deviation for each raw radar signal is calculated. This Standard Deviation information is exploited to estimate the speed of a target. This method shows a good result in estimating the vehicle speed crossing FSR baseline. By analyzing 850 experimentally obtained car signatures, the performance of the system is evaluated and the effectiveness of the system is confirmed.